Kandungan dan Ketebalan Endapan Nikel Laterit di Kecamatan Langgikima Kabupaten Konawe Utara Provinsi Sulawesi Tenggara - Hasria Hasria; Rino Erwin; Ali Okto; Bahdad Bahdad; Arisona Arisona; La Hamimu (Universitas Muslim Indonesia, 2023)
This study is located in Lameruru Village, Langgikima District, North Konawe Regency, Southeast Sulawesi Province. The research area consists of morphological units of low hills and hills with an altitude of 200 to 350 meters above sea level. This study aims to determine the morphological conditions and analyze the thickness of laterite nickel deposits based on the morphological conditions in the study area. The morphological observation method was based on morphometric analysis and morphographic analysis, while the thickness analysis of laterite nickel deposits was based on exploration drill data consisting of collar data, lithological data, survey data, and assay data. The analytical method used in this study is the XRF (X-Ray fluorescence) geochemical method to determine the elemental content based on the percentage content of the laterization zone in the study area. The results of the study show that the morphology in the study area was divided into low hills and hills with slightly sloping, sloping, slightly steep, and steep slopes. The thickness of laterite nickel deposits in the study area follows the shape of the topographical slope where in areas with a higher slope level the nickel deposits formed are thinner and the lower the slope level the thicker nickel deposits are formed.